Islamic-Based Anti-Corruption Education: Internalization of Islamic Social Ethics at Muhammadiyah Kayen Elementary School - Norma Qur’ani; Suyitno; Abdulazis Kalupae (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2026)
Corruption remains a crucial issue in Indonesia that requires preventive measures through education, starting with elementary school. Although many studies discuss the inclusion of anti-corruption values, analysis of the pedagogical process of internalizing these values in daily practice is still limited. This qualitative case study aims to analyze the mechanisms of internalizing the values of honesty (shiddiq), justice ('adalah), responsibility (amanah), and caring through Al-Islam learning at Muhammadiyah Kayen Condongcatur Elementary School, Yogyakarta. Data were collected through in-depth interviews, observations, and documentation of the principal, teachers, and students, then analyzed using an interactive model. The results show that the internalization of values takes place in an integrated educational ecosystem, not through a single strategy. The process includes integration into learning and school culture, role modeling, habituation, verbal persuasive approaches (advice, ibrah, and amtsal), and strengthening discipline through supervision, educational sanctions, and rewards. These findings confirm that a religious school environment supports the contextual and sustainable internalization of anti-corruption values. The novelty of this research lies in its holistic analysis of the mechanism of internalizing Islamic social ethical values that are fully integrated with the school ecosystem, contributing to the development of anti-corruption education and character education models in elementary schools.